2008
DOI: 10.1152/physiolgenomics.00256.2007
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide discovery of Pax7 target genes during development

Abstract: Pax7 plays critical roles in development of brain, spinal cord, neural crest, and skeletal muscle. As a sequence-specific DNA-binding transcription factor, any direct functional role played by Pax7 during development is mediated through target gene selection. Thus, we have sought to identify genes targeted by Pax7 during embryonic development using an unbiased chromatin immunoprecipitation (ChIP) cloning assay to isolate cis-regulatory regions bound by Pax7 in vivo. Sequencing and genomic localization of a lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 84 publications
0
19
0
Order By: Relevance
“…Identification of Pax7 transcription factor targets in E16 mouse embryos revealed several genes involved in the regulation of proliferation 51 . Among them were genes positively impacting cell proliferation, such as CntfR , receptor of CNTF – a member of IL-6 family, which induces Jak/STAT and Ras/MAPK signaling, 52 Camk1d involved in calcium-calmodulin dependent signaling, 53 as well as Frk which also regulates cell cycle progression 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Identification of Pax7 transcription factor targets in E16 mouse embryos revealed several genes involved in the regulation of proliferation 51 . Among them were genes positively impacting cell proliferation, such as CntfR , receptor of CNTF – a member of IL-6 family, which induces Jak/STAT and Ras/MAPK signaling, 52 Camk1d involved in calcium-calmodulin dependent signaling, 53 as well as Frk which also regulates cell cycle progression 54 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we identified Cbln4 as a direct target gene of SRY by employing in vivo ChIP analysis. In vivo ChIP is a powerful tool for studying protein-DNA interactions [50,51], offering the unique possibility of identifying novel target genes and their potential regulatory regions [52,53]. However, because of the occurrence of random protein-DNA cross-linking, nonspecific DNA fragments are likely to be precipitated together with the DNA genuinely bound by the protein of interest.…”
Section: Discussionmentioning
confidence: 99%
“…In skeletal muscle, many genes are involved in regenerative pathways, either by maintaining the integrity of the tissue and favoring skeletal myogenesis, as is the case for collagen, type XIX, alpha 1 ( Col19a1 ) [29], or by promoting muscle differentiation and regeneration, as is the case for the paired box gene ( Pax7 ), myogenic differentiation 1 ( Myod1 ), myogenic factor 5 ( Myf5 ), myocyte enhancer factor 2C ( Mef2c ) and myogenin ( Myog ) [30], [56][60].…”
Section: Methodsmentioning
confidence: 99%